Technique analysis of German youth elite athletes in cross-country skiing - Fudel, R.; Krämer, F.; Unger, F. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Technique training is a fundamental part of long-term athlete development in cross-country (XC) skiing and an important determinant of performance in elite sports. However, technical perfor mance of youth athletes is rarely considered neither in competition systems nor talent identifica tion or scientific research. Thus, the aim of this study was to evaluate the technical performance level of German youth elite athletes while skiing in competition.186 youth elite XC skier (m 99 / w 87, Ø 14,5 yrs) were captured in an 2.2 km individual race of the German Youth Cup in January 2020 in Reit im Winkl. Two high-speed cameras recorded the athletes from frontal and sagittal view while performing skating V2 on a 15m flat part of the track. Three experts evaluated their technical quality based on five movement characteristics. The Mc Nemar test was applied to check for statistical differences between the assessed criteria and Mann-Whitney-U test for differences in age, sex or performance level. The main fault among all participants appears in insufficient hip extension and forward leaning in the initial position (2= 7.89, p=.001). There are no significant differences between age groups (Z= -1.840, p= .066), sex (Z= -1.419, p= .156) or performance level in competition.Our project provides individual feedback for athletes and coaches about their current techni cal performance level as well as general knowledge to improve technique training in youth XC skiing. A specially developed software can be used to create a practical assessment scheme for analysing technical characteristics in training, competition or talent identification.